Clinical features of the metabolic syndrome in adolescents: minor role of the Trp64Arg β3 -adrenergic receptor gene variant - Porto, Patricia Inés (2004)
Obesity and hypertension are increasing medical problems in adolescents. We evaluated the association between being overweight-particularly abdominal fat-and having hypertension and assessed the contribution of the Trp64Arg β3-adrenergic receptor gene variant. In a population-based study, we determined family history, anthropometric variables, and arterial blood pressure of 934 high school students, out of whom we selected 121 normotensive and 54 hypertensive students. Biochemical measurements included circulating renin and angiotensin-converting enzyme activities, leptin, glucose, insulin and lipid levels, and β3-adrenergic receptor genotypes. We used Mann-Whitney U test, χ2-test, and Spearman rank-order correlation. In the total population, hypertension prevalence increased across the entire range of body mass index (BMI) percentiles. In the sample, hypertensive students showed higher BMI, waist-to-hip ratio, triglycerides, and insulin resistance and lower HDL-cholesterol than normotensive students did. Age- and sex-adjusted systolic arterial blood pressure was correlated with BMI, waist-to-hip ratio, insulin resistance, and leptin. Leptin was correlated with BMI and homeostasis model assessment method. We found no association among hypertension, BMI, and leptin levels with β3-adrenergic receptor genotypes. Especially in girls, the waist-to-hip ratio was, however, suggestively higher in Arg64 variant carriers than in noncarriers, independent of hypertension. In fact, there was a significantly (p < 0.01) higher frequency of carriers of the Arg64 variant across the waist-to-hip ratio quartiles. In adolescents of European origin, hypertension is associated with an increased degree of obesity among other characteristics of the metabolic syndrome; the Trp64Arg variant of the β3-adrenergic receptor gene may favor the central adiposity gain.